Stromal reaction inhibitor and immune-checkpoint inhibitor combination therapy attenuates excluded-type colorectal cancer in a mouse model. (1st February 2021) - Yorita, Naoki; Yuge, Ryo; Takigawa, Hidehiko; Ono, Atsushi; Kuwai, Toshio; Kuraoka, Kazuya; Kitadai, Yasuhiko; Tanaka, Shinji; Chayama, Kazuaki
Abstract: Despite recent advances in cancer immunotherapy, the efficacy of colorectal cancer (CRC) immunotherapy regimens is limited. This study evaluated the combined effect of an anti-PD-1 antibody and a platelet-derived growth factor receptor inhibitor (imatinib) on CRC progression using an orthotopic transplanted mouse model that reproduced the three histological phenotypes of CRC (inflamed-, excluded-, and desert-type). The frequency of each of these phenotypes in 196 human CRC tissue samples was also evaluated. Excluded-type CRC had the highest frequency in human tissue samples. In the mouse model, imatinib suppressed stromal reaction and increased sensitivity to anti-PD-1 treatment in excluded-type CRC. Antitumor effect was observed in mice with excluded-type tumors only after concomitant administration of anti-PD-1 antibody and imatinib. Immunohistological analysis revealed a reduction in stromal volume and an increase in the number of CD8-positive T cells in the tumor nest following combination therapy. RNA sequencing revealed significant activation of immune-related pathways and suppression of stromal-related pathways in transplanted tumors treated with combination therapy compared with tumors treated with anti-PD-1 antibody monotherapy. This combination therapy may prove effective for CRC cases that are unresponsive to anti-PD-1 antibody monotherapy. Highlights: Mouse model represented all three tumor-immunity-associated histological phenotypes. ICI and PDGFR inhibitors were evaluated alone and in combination. Effect on tumor inhibition was evaluated in each histological phenotype. Combination therapy was effective for treating tumor growth in excluded-type CRC.